Grand gestures - Alcoreza, Kimberly B. 1988- (2013)
"Historically, cinema has not been kind to the community of little people. Grand Gestures attempts to recify this with a story that celebrates little people, and at the same time brings to light some of the tissues that they face. Gary is a little person who runs a salon with his best friend, Clifford. In a place where looks and appearances are important, Gary faces another challenge: how to make an average-sized girl fall in love with him. Greta, one of the stylists at the salon, likes to dress up as different characters everyday. Despite her concern for appearances, she and Gary have an inevitable friendship thanks to the offbeat family the salon provides. As Gary tries to convince his mother, Hilda, to acknowledge the health issues her dwarfism causes, his insecurities also begin to surface. The story is a romantic comedy-campy, and even absurd at times, but full of characters who share a genuine friendship. Everybody is in some way vain an conceited, but Gary is the anomaly that reveals that they are nonetheless capable of respect, friendship, loyalty and love."